2004
DOI: 10.1149/1.1705661
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Structure and Chemical Composition of Crystalline and Amorphous Electroless Ni-W-P Coatings

Abstract: Electroless deposition was applied to prepare Ni-W-P coatings of two types: crystalline, with low P and W, and amorphous with high W content. Their morphology was studied by atomic force microscopy. Polycrystalline Ni-W-P alloys consist of grains of stacked plates ͑lamellas͒, as it was revealed by transmission electron microscopy. The coatings exhibit a ͗100͘ texture. X-ray diffraction and electron diffraction analysis demonstrated the unit cell parameter of the crystalline phase in Ni-W-P is practically equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…3), which matches up with selected diffraction peaks of nickel powder. Valova et al [14] have reported similar findings that NiWP possesses almost identical diffraction peaks as nickel. According to the diffraction pattern shown in Fig.…”
Section: Article In Pressmentioning
confidence: 57%
See 1 more Smart Citation
“…3), which matches up with selected diffraction peaks of nickel powder. Valova et al [14] have reported similar findings that NiWP possesses almost identical diffraction peaks as nickel. According to the diffraction pattern shown in Fig.…”
Section: Article In Pressmentioning
confidence: 57%
“…However, there are only few reports available in open literature discussing physicochemical properties of bulky NiWP deposits [7,[11][12][13][14]. None of them has embraced the magnetic properties of NiWP particles in submicron and nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches show that the presence of phosphorus in iron alloys influences on tribological properties and its corrosion resistance [12]. The amorphous Ni-W-P alloy with high strength properties was obtained [13,14]. Introduction of phosphorous into the alloys, for example Co-W, eliminates the cracks even at higher current densities applied for electrodeposition [15].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] This suggests that the codeposition of Re is possibly going in two different ways. One of them is probably similar to the cases mentioned above: the reduction of Re ions proceeds on the surface of the nanograins during the film growth.…”
Section: D454mentioning
confidence: 99%